Usted pregunta (Journal of Parents and Teachers, 2025)
This time, Joaquín is not answering questions. The questions are directed at the reader through specific situations involving children and teenagers. It is a game in which parents are presented with these situations and asked to give their first response. For example, what would be your first reaction if your 13-year-old son told you that he no longer wants to study and wants you to help him find a job? Or, how would you react if your 17-year-old daughter suddenly told you that in a few months she will be joining a religious congregation? What if your daughter told you she needed money to help her 18-year-old friend who wants to have an abortion? These are important situations to consider, just in case they arise!
Keywords: children, teenagers, parents, real-life situations.